Encyclopedia of educational leadership and administration (Sage Publications, 2006)
Presents the theories, research, terms, concepts, ideas, and histories on educational leadership and school administration, as it is taught on PGCE courses and practiced in schools and colleges. With over 600 entries, the two-volumes of this encyclopedia represent the knowledge base of educational leadership and school administration.